Colectivo de trabajo y reglas de oficios. Cooperación entre jóvenes y viejos, hombres y mujeres en las brigadas de Policía de socorro - Sandrine Caroly; Marc Loriol; Valérie Boussard (Universidade do Porto, 2006)
Brought about by a study on the construction of stress in the police profession, our observations of the work relations between young and old, as well as between men and women in different brigades created in several commissariats (on the outskirts of Paris and in the province), provides information on the forms and dynamics of construction of this profession. The police profession currently suffers profound mutations, with alterations in the problems of the populations with which they are occupied, and with evolutions in the public politics of security. The tensions, the conflicts and/or the relations of mutual aid, of cooperation in daily work between the wage-earners according to their diversity (seniority, gender) are indicators of the good functioning of work collectives. Learning the police profession depends on the work relations at the heart of the collectives, presenting possibilities of construction of experiences and the means to preserve their health.